Identification of BRAF V600E mutation in odontogenic tumors by high-performance MALDI-TOF analysis - Lucrezia Togni; Antonio Zizzi; Roberta Mazzucchelli; Andrea Santarelli; Corrado Rubini; Marco Mascitti (Nature Publishing Group, 2022)
Abstract Odontogenic tumors are rare lesions with unknown etiopathogenesis. Most of them are benign, but local aggressiveness, infiltrative potential, and high recurrence rate characterize some entities. The MAP-kinase pathway activation can represent a primary critical event in odontogenic tumorigenesis. Especially, the BRAF V600E mutation has been involved in 80-90% of ameloblastic lesions, offering a biological rationale for developing new targeted therapies. The study aims to evaluate the BRAF V600E mutation in odontogenic lesions, comparing three different detection methods and focusing on the Sequenom MassARRAY System. 81 surgical samples of odontogenic lesions were subjected to immunohistochemical analysis, Sanger Sequencing, and Matrix-Assisted Laser Desorption/Ionization-Time of Flight mass spectrometry (Sequenom). The BRAF V600E mutation was revealed only in ameloblastoma samples. Moreover, the presence of BRAF V600E was significantly associated with the mandibular site (ρ = 0.627; P value <0.001) and the unicystic histotype (ρ = 0.299, P value <0.001). However, any significant difference of 10-years disease-free survival time was not revealed. Finally, Sequenom showed to be a 100% sensitive and 98.1% specific, suggesting its high-performance diagnostic accuracy. These results suggest the MAP-kinase pathway could contribute to ameloblastic tumorigenesis. Moreover, they could indicate the anatomical specificity of the driving mutations of mandibular ameloblastomas, providing a biological rational for developing new targeted therapies. Finally, the high diagnostic accuracy of Sequenom was confirmed.